2010
DOI: 10.1093/annonc/mdp394
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal symptoms in women undergoing chemotherapy-induced and natural menopause: a prospective controlled study

Abstract: Women undergoing chemotherapy-induced menopause may experience worse symptoms than women undergoing natural menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 15 publications
6
29
0
3
Order By: Relevance
“…This result supports the findings of a report that breast cancer patients may experience worse menopausal symptoms than women undergoing natural menopause [25]. Menopausal symptoms after anti-carcinogenic therapy are similar to those experienced naturally.…”
Section: Discussionsupporting
confidence: 90%
“…This result supports the findings of a report that breast cancer patients may experience worse menopausal symptoms than women undergoing natural menopause [25]. Menopausal symptoms after anti-carcinogenic therapy are similar to those experienced naturally.…”
Section: Discussionsupporting
confidence: 90%
“…There were no between group differences in age, minority status, or education level ( Table 2). There were significantly more women in the BC group who were postmenopausal compared with the HC group, which was expected given that chemotherapy can induce early menopause (38). There were no differences between the C+ and C− groups in menopausal status, time off-therapy, radiation, or tamoxifen, although the C+ group had significantly higher disease stage at diagnosis, as expected ( Table 2).…”
Section: Methodssupporting
confidence: 68%
“…However, Amir et al [12], found that the breast cancer treatments, like chemotherapy and endocrine therapy, may lead to a higher risk of developing the same health complaints. Though, the physiology of the menopause is complex, and may vary considerably both among patients and healthy women [13,14].…”
Section: Introductionmentioning
confidence: 99%